Pharmacological Vitamin C Treatment Impedes the Growth of Endogenous Glutamine-Dependent Cancers by Targeting Glutamine Synthetase - Long, Yali; Qiu, Jia; Zhang, Bing; He, Peng; Shi, Xinchong; He, Qiao; Chen, Zhifeng; Shen, Wanqing; Li, Zhoulei; Zhang, Xiangsong (Frontiers in Pharmacology, 2021)
Purpose: Glutamine synthetase (GS) is the only currently known enzyme responsible for synthesizing endogenous glutamine (Gln). GS exerts a critical role in the oncogenesis of endogenous Gln-dependent cancers, making it an attractive target for anti-tumor therapies. A mixed-function oxidation system consisting of vitamin C (VC), oxygen, and trace metals can oxidize GS and promote its degradation. The current study aims to explore the effect of pharmacological VC treatment on GS. Methods: Endogenous Gln-dependent cancer lines (breast cancer MCF7 and prostate cancer PC3) were selected to establish chronic Gln-deprived MCF7 and PC3 cell models. The expression of GS in parental and chronic Gln-deprived tumor cells exposed to VC treatment and control was determined by Western blot analysis. The anti-cancer effects of VC on parental and chronic Gln-deprived tumor cells were assessed by CCK-8 and annexin V-FITC/PI FACS assays. In addition, changes in cellular reactive oxygen species (ROS), glutathione (GSH) levels and NADPH/NADP+ ratio were analyzed to explore the underlying mechanisms. Moreover, BALB/c nude mice xenografting with parental and chronic Gln-deprived prostate cancer cells were constructed to evaluate the in vivo therapeutic effect of VC. Finally, tumor 13N-ammonia uptake in mice bearing prostate cancer xenografts was analyzed following treatment with VC and the expression of GS in xenografts were detected by immunohistochemistry. Results: Cells overexpressing GS were obtained by chronic Gln deprivation. We found that the cytotoxic effect of VC on cancer cells was positively correlated with the expression of GS. Additionally, VC treatment led to a significant increase in ROS production, as well as GSH depletion and NADPH/NADP+ reduction. These changes could be reversed by the antioxidant N-acetyl-L-cysteine (NAC). Furthermore, pharmacological VC treatment exhibited a more significant therapeutic effect on xenografts of prostate cancer cells overexpressing GS, that could be well monitored by 13N-ammonia PET/CT imaging. Conclusions: Our findings indicate that VC can kill cancer cells by targeting glutamine synthetase to induce oxidative stress. VC could be used as an anti-cancer treatment for endogenous glutamine-dependent cancers.